The Impact of Job Satisfaction on Commitment - Oka, Ardian; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
HR is an abbreviation of "Human Resources". This term is generally used in the context of organizational or corporate management to refer to the department or function responsible for managing aspects related to human resources, such as recruitment, training, employee development, performance management, and personnel administration needs to be paid attention to by the leadership of an organization or company in providing maximum service and satisfaction to the community, for this reason skilled and reliable human resources are needed Work has a positive and significant effect. on Employee Commitment with an original sample value of 0.303 and ap value of 0.004. HR Quality has a positive and significant effect on Job Satisfaction with an original sample value of 0.459 and an original sample value of 0.001 0.222 and p value of 0.052 original sample value of 0.443 and ap value of 0.002. Work Motivation has a positive and significant effect on Employees Commitment with an original sample value of 0.370 and ap value of 0.003. HR quality has a positive and significant effect on employee commitment through job satisfaction with an original sample value of 0.139 and ap value of 0.006. Work Motivation has a positive and insignificant effect on Employee Commitment through Job Satisfaction with an original sample value of 0.134 and ap value of 0.055.